ALLOCATION OF THE EU FUNDS AND THE DEVELOPMENT LEVEL OF COMMUNES IN RURAL AREAS OF THE MAŁOPOLSKA PROVINCE - Żmija, Katarzyna (Acta Scientiarum Polonorum. Oeconomia, 2015)
Due to the specific problems of the rural areas in the Małopolska Province, the measures directed at the support of their multifunctional development are of a particular importance. Such measures are one of the principal aims of the rural areas development policy. This paper is an attempt to determine the direction of the spatial allocation of the funds received in the framework of the selected measures within the Rural Development Program (PROW) in the years 2007-2013, assigned to the support of the multifunctional development of rural areas, taking into account the socio-economic development level of the communes in the rural areas of the Małopolska Province. The results of the study suggest a territorial variations in the funds' absorption and the existence of significant differences in this respect among the studied communes. However, on the level of individual communes, no relationships among the socio-economic development level of a commune and the total value of the subsidies obtained by the beneficiaries in the commune were revealed.